The Inheritance Verses: A Comparative Study of Zaitunah Subhan’s and Henri Shalahuddin’s Interpretations - Bannan Naelin Najihah; Hilda Yanti Safitri (Journal of Ulumul Qur'an and Tafsir Studies, 2022)
This article discusses the comparison of the interpretations of Zaitunah Subhan (feminist Muslim) and Henri Salahuddin (conservative occidentalist Muslim) regarding inheritance verses. The lack of comparative studies of Muslim feminist and conservative Muslim interpretations of the inheritance verse encourages the importance of studying this matter. This study uses a qualitative comparative study method with a literature review approach. The data sources are the book "The Hatred Interpretation" and the dissertation "Discourse on Gender Equality in Islamic Thought at State Islamic Universities in Indonesia: Case Studies at Sunan Kalijaga State Islamic University, Yogyakarta". Data collection techniques using search methods and data analysis techniques using content analysis. This article finds that there are three aspects of similarities and seven aspects of differences between Zaitunah Subhan and Henri in understanding inheritance verses. The similarities are in the distribution of inheritance rights between men and women which can change according to the conditions stipulated in the Qur'anic text, consideration of aspects of gender justice and consideration of aspects of economic responsibility as the cause of differences in inheritance rights. The differences are the methodological aspect, the editorial content of the verse (dalālat al-Qur'ān), the assessment of the character of the verse, the maximum-minimum limit for the distribution of inheritance, the portion of the division of inheritance and the relationship of the verse to social reality and the scientific clump approachment. This article is intended to increase knowledge about the rich variety of interpretations of inheritance verses related to gender issues in it.